The Effect of Digital Marketing Strategies, Social Media, and Influencer Marketing on Brand Awareness - Ramdani, Amjad; Fietroh, Muhammad Nur (Journal of Educational Management Research, 2025)
This study aims to analyze the influence of digital marketing, social media, and influencer marketing on brand awareness of MSME products. The background of this study is based on the low level of brand awareness, which remains a major challenge in developing the competitiveness of MSMEs, especially in non-metropolitan areas. Using a quantitative approach and an explanatory survey method, data was collected from 100 SME respondents who actively use social media in their marketing strategies. The research instrument was validated through validity and reliability tests, then analyzed using multiple linear regression with SPSS version 25. The results indicate that the three independent variables—digital marketing, social media, and influencer marketing—have a positive and significant impact on brand awareness. Digital marketing has been proven to efficiently enhance brand visibility; social media strengthens emotional connections and closeness between brands and consumers; while influencer marketing provides credibility effects that expand brand reach through social influence. The coefficient of determination (Adjusted R²) of 0.645 indicates that the model explains 64.5% of the variance in brand awareness. This study provides practical contributions for SMEs in designing more effective and adaptive digital marketing strategies in response to changes in digital consumer behavior.